RANCANGAN APLIKASI KOMUNIKASI GROUND TO GROUND MENGGUNAKAN CLIENT VOICE OVER INTERNET PROTOCOL (VOIP) - Raihan Dimas Muharam; Muh Wildan; Irvan, Irvan (CV SWA Anugerah, 2024)
Telecommunications technology is currently developing leading to Internet-based technology, for example the Internet Protocol. Voice Over Internet Protocol (VoIP) is a user that routes messaging, voice, and video services to an Internet Protocol network and connects to the network IP. Benefits, bandwidth efficiency, cost management efficiency.The purpose of this design is for Ground to Ground communication media at Pasir Pengaraian Airport, which does not yet have a Ground to Ground communication medium, only uses a mobile phone via Whatsapp which does not yet have an automatic record in the application, with a client application design where this application is equipped with VoIP-based telephone services. and also records of Ground to Ground communication conversations can be a Ground to Ground communication medium at Pasir Pengaraian Airport, with a simple design and relatively efficient cost, VoIP-based communication can be an alternative communication for all airports in Indonesia, Therefore the author makes VoIP communication design based on Raspberry Pi as a server using the Asterisk operating system and the client using an application designed with Android Studio configured with a Raspberry Pi server, using this client-server interconnection